Effects of an Erbium:Yttrium‐Aluminum‐Garnet Laser and Ultrasonic Scaler on Titanium Dioxide‐Coated Titanium Surfaces Contaminated With Subgingival Plaque: An In Vitro Study to Assess Post‐Treatment Biocompatibility With Osteogenic Cells. Issue 11 (1st November 2017) - Giannelli, Marco; Bani, Daniele; Tani, Alessia; Materassi, Fabrizio; Chellini, Flaminia; Sassoli, Chiara
Abstract : Background: Effects of conventional ultrasonic scaler versus an erbium:yttrium‐aluminum‐garnet (Er:YAG) laser on titanium surfaces contaminated with subgingival plaque from patients with peri‐implantitis are evaluated in terms of: 1) plaque and biocorroded titanium oxide coating removal; 2) surface change induction; and 3) residual biocompatibility toward osteoblasts. Methods: Subgingival plaque‐coated titanium disks with a moderately rough surface were fixed with ethanol and treated with an ultrasonic scaler (metal tip) or Er:YAG laser (20.3 or 38.2 J/cm 2 ) in non‐contact mode. Fluorescent detection of residual plaque was performed. Disk surface morphology was evaluated by scanning electron microscopy. Viability, attachment, proliferation, and differentiation of Saos‐2 osteoblasts on new and treated disks were assayed by propidium iodide/DNA stain assay and confocal microscopic analysis of cytoskeleton, Ki67, expression of osteopontin and alkaline phosphatase, and formation of mineralized nodules. Results: Both methods resulted in effective debridement of treated surfaces, the plaque area being reduced to 11.7% with the ultrasonic scaler and ≤0.03% with the Er:YAG laser (38.2 J/cm 2 ). Ultrasound‐treated disks showed marked surface changes, incomplete removal of the titanium dioxide (TiO2 ) layer, and scanty plaque aggregates, whereas the Er:YAG laser (38.2 J/cm 2 ) completely stripped away the plaque and TiO2 layer, leaving a micropitted surface. Both treatments maintained a good biocompatibility of surfaces to Saos‐2 osteoblasts. Air‐water cooling kept disk temperature below the critical threshold of 47°C. Conclusion: This study shows that an ultrasonic scaler with metal tip is less efficient than high‐energy Er:YAG irradiation to remove the plaque and TiO2 layer on anodized disks, although both procedures appear capable of restoring an adequate osseoconductivity of treated surfaces.